Larval zebrafish swim bouts in three dimensions reveal both new and redundant behaviours - Ravan, Aniket; Chemla, Yann R; Gruebele, Martin (Journal of the Royal Society interface, 2025)
Two-dimensional swimming of larval zebrafish has been studied extensively. We use a three-dimensional imaging system and neural network for pose estimation to study their three-dimensional behaviour. We answer two questions: (i) are spontaneous or delayed-onset turns from free swim, dark flash and acoustic startle experiments objectively differentiable? and (ii) could larvae use stochastic selection among responses, 'feinting' during an escape? Our analysis identifies two new major modes of dorso-ventral displacement. The first half-cycle of swim bouts contains most of the information to distinguish behaviours. Dimensionality reduction as previously applied to nematodes and fruit flies reveals four clusters of swimming behaviour: the previously classified short-latency C-turns (SLCs), O-turns, free swims and a behaviour we term 'voluntary turn', which comprises turns during free swimming and time-delayed turns during dark flash and acoustic startle experiments that cannot be distinguished even when additional half-cycles are included in the analysis. Unlike previous clustering analyses, we provide a physical picture of behavioural clusters in terms of two coordinates. The larvae also engage in a new behaviour: the vertical component of the SLC enables the animal to either extend the initial direction or switch it in the middle. We rationalize this behaviour as a feinting response for predator evasion.